2016
DOI: 10.1016/j.ejsobi.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between ammonia-oxidizing communities, soil methane uptake and nitrous oxide fluxes in a subtropical plantation soil with nitrogen enrichment

Abstract: a b s t r a c tAmmonia-oxidizers play an essential role in nitrogen (N) transformation and nitrous oxide (N 2 O) emission in forest soils. It remains unclear if ammonia-oxidizers affect interaction between methane (CH 4 ) uptake and N 2 O emission. Our specific goal was to test the impacts of changes in ammoniaoxidizing communities elicited by N enrichment on soil CH 4 uptake and N 2 O emission. Based on a field experiment, two-forms (NH 4 Cl and NaNO 3 ) and two levels (40 and 120 kg N ha À1 yr À1 ) of N were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The higher archaeal amoA gene copy number compared to bacterial amoA could be linked to the acidic soil pH (<4.5 in all treatments) 43 . This phenomenon has been widely observed in previous soil studies, and may be explained by the fact that NH 3 content is reduced at lower pH and ammonia-oxidizing Archaea have a higher affinity for NH 3 than ammonia-oxidizing bacteria 18 .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The higher archaeal amoA gene copy number compared to bacterial amoA could be linked to the acidic soil pH (<4.5 in all treatments) 43 . This phenomenon has been widely observed in previous soil studies, and may be explained by the fact that NH 3 content is reduced at lower pH and ammonia-oxidizing Archaea have a higher affinity for NH 3 than ammonia-oxidizing bacteria 18 .…”
Section: Discussionsupporting
confidence: 61%
“…The absence of a correlation between levels of functional genes and gas fluxes is surprising because correlations between the nosZ , archaeal amoA , and bacterial amoA genes and N 2 O fluxes have previously been described in forest systems 16 18 . The quantification results for pmoA may explain CH 4 fluxes, as this gene has been shown to be positively correlated to CH 4 emissions from soil 17 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these impacts were not reproduced by all of the six models except for the DELM and NOE 195 models. Previous study showed that the impacts of NH4 + addition on N2O emissions are, to some extent, larger compared with NO3 -addition (Wang et al, 2016). This is probably due to two primary reasons.…”
Section: Model Performancementioning
confidence: 83%
“…Furthermore, soil microorganisms can be affected by multiply factors such as climate, soil physical, and chemical properties, and substrate quantity and quality [20,21]. Several studies reported that soil microbial community structure and diversity are strongly impacted by warming and N fertilization, and play an important role on controlling soil CO 2 and N 2 O fluxes [17,22,23]. However, convincing data about the direct link of soil GHG fluxes and soil microbial characteristics under warming and N fertilization are still scarce.…”
Section: Introductionmentioning
confidence: 99%